Adrenocortical failure in diabetic pregnancy. Issue 672 (October 1981) - Soler, Norman G.
Abstract : A Caucasian class F diabetic developed features suggestive of adrenocortical insufficiency during the second half of pregnancy. Serial biochemical and hormonal studies confirmed a diagnosis of progressive primary adrenal failure. Replacement therapy was introduced at 31 weeks' gestation and the pregnancy ended successfully 6 weeks later. Addison's disease is another autoimmune disorder that may occur in association with diabetic pregnancy.